Function Value Analysis of the Technology Transfer System - Simanauskas, Leonas; Maceika, Augustinas (Ekonomika, 2002)
The main goal of this work is to review application of functional value analysis method for creating and evaluating types of technology transfer system. Definition of the technology transfer functions and expenditures for his implementation is done with importance rating. The system improvement directions can be made due comparing the expenditures necessary to implement functions with importance to the transfer processes. There were found that better results give technology transfer system with specialised organisations consists of: technology spreaders, technology consumers, state government organisations, support enterprises and financial organisations. The activity and co-operation of this specialised make possible development of technology transfer and reduce risk. The support of state government, finance institutions, innovation centres, business incubators and technology parks helps to carry out technology transfer in the most cost effective and productive way. We proposed method of system’s evaluation and checked on four different versions of system.